The Effectiveness of Traditional Mediation as an Alternative for Resolving Family Disputes in the National Legal System - Roziqin; Answar; Harry Tuhumury; Najamuddin Gani; Zonita Zirhani Rumalean (Ekasakti Journal of Law and Justice, 2026)
Customary mediation is a dispute resolution mechanism based on local wisdom values ​​that has long been practiced in Indonesian customary law communities, particularly in resolving family disputes. This study aims to analyze the effectiveness of customary mediation as an alternative for resolving family disputes within the national legal system, identify the structural and cultural barriers encountered, and formulate an appropriate integration model between customary law and state law. This study uses normative legal research methods with statutory, conceptual, and comparative approaches. The results show that customary mediation has proven effective in creating post-dispute relational harmony and has a high level of compliance because it is based on communal agreements respected by all parties. However, customary mediation faces challenges in terms of legal certainty, guaranteeing the protection of individual rights, and formal recognition in the judicial system. Integrating customary mediation into national law through a structured legal pluralism mechanism is a strategic step to strengthen access to justice for indigenous communities.